Attributivity and Subjectivity in Czech Journalism and Scientific Literature - Kubát, Miroslav; Čech, Radek (Bohemistyka, 2024)
This study examines two recently proposed stylometric indices, attributivity and subjectivity, in the context of Czech journalism and scientific literature. Index of attributivity is defined as the ratio of the frequency of attributes to the sum of frequencies of nouns, pronouns, and attributes. Index of subjectivity is defined as the ratio of the frequency of subjects to the sum of frequencies of predicates and subjects. The research is based on the corpus of contemporary written Czech language SYN2020. It appears that both indices of attributivity and subjectivity are sensitive to different genres, and could be used in stylometric analyses, especially those that focus on the interpretability of quantitative measures. In general, more formal texts tend to have higher values of both indices across different genres.